Co-Morbidities of Interstitial Cystitis - Chelimsky, Gisela; Heller, Elizabeth; Buffington, C. Anthony; Rackley, Raymond; Zhang, Di; Chelimsky, Thomas (Frontiers in Neuroscience, 2012)
Introduction: This study aimed to estimate the proportion of patients with Interstitial Cystitis/Painful Bladder Syndrome (IC/BPS) with systemic dysfunction associated co-morbidities such as irritable bowel syndrome (IBS) and fibromyalgia (FM). Material and Methods: Two groups of subjects with IC/BPS were included: 1) Physician diagnosed patients with IC/BPS and 2) Subjects meeting NIDDK IC/PBS criteria based on a questionnaire (ODYSA). These groups were compared to healthy controls matched for age and socio-economic status. NIDDK criteria required: pain with bladder filling that improves with emptying, urinary urgency due to discomfort or pain, polyuria > 11 times/24 hrs, and nocturia > 2 times/night. The ODYSA instrument evaluates symptoms pertaining to a range of disorders including chronic fatigue, orthostatic intolerance, syncope, IBS, dyspepsia, cyclic vomiting syndrome, headaches and migraines, sleep, Raynaud’s syndrome and chronic aches and pains. Results: IC/BPS was diagnosed in 26 subjects (mean age 47 +/- 16 yrs, 92% females), 58 had symptoms of IC/BPS by NIDDK criteria, (mean age 40 +/- 17 yrs, 79% females) and 48 were healthy controls (mean age 31+/- 14 yrs, mean age 77%). Co-morbid complaints in the IC/BPS groups included gastrointestinal symptoms suggestive of IBS and dyspepsia, sleep abnormalities with delayed onset of sleep, feeling poorly refreshed in the morning, waking up before needed, snoring, severe chronic fatigue and chronic generalized pain, migraines and syncope. Discussion: Patients with IC/BPS had co-morbid central and autonomic nervous system disorders. Our findings mirror those of others in regard to IBS, symptoms suggestive of FM, chronic pain and migraine. High rates of syncope and functional dyspepsia found in the IC/BPS groups merit further study to determine if IC/BPS is part of a diffuse disorder of central, autonomic and sensory processing affecting multiple organs outside the bladder.